Teknologi dan Ujaran Kebencian: Serangan di Kolom Komentar Instagram - Larasati, Annida Nur Iffah (Magister Komunikasi Universitas Sultan Ageng Tirtayasa, 2024)
Hate speech via the Instagram comments column can vary depending on the individual committing the act and the specific context. Some people may use hate speech as a way to demonstrate power or dominance over another individual or group. By insulting or demeaning certain groups, they may attempt to assert their superiority in the social hierarchy. Based on the Spiral of Silence theory proposed by Elisabeth Noelle-Neuman, in the context of hate speech on Instagram, these assumptions can help explain the phenomenon of the dominance of negative comments and provide insight into handling strategies. Education about internet etiquette and digital empathy is also important. Teaching users, especially younger generations, about how to provide constructive feedback and avoid negative behavior online can help create a more positive digital environment. Only with the combined efforts of individuals, communities, and social media platforms can we reduce the negative impact of social media abuse and promote healthier, more constructive communication.